Detecting In-Vitro Colistin Resistance- A Comparative Study Between Broth Microdilution Versus Vitek-2 For Colistin Susceptibility Testing - Butta, Hena; Mendiratta, Leena; Sardana, Raman; Gilotra, Kirti; Hasan, Sana; Kansal, Sudha; Chatterjee, Suranjit (Annals of Pathology and Laboratory Medicine, 2020)
Background: Susceptibility testing for polymyxins is a great challenge for a Clinical Microbiology laboratory. There are several methodological issues associated with MIC (Minimum Inhibitory Concentration) determination of colistin. Methods: In our study, we have compared the results of colistin susceptibility testing by Automated system (Vitek-2, Biomerieux, France) with the reference Broth Microdilution method (BMD) to identify the type of discrepancies by Vitek-2 method and thus develop a practical and accurate approach for colistin susceptibility testing in a Clinical Microbiology laboratory. A total of 730 strains of Gram negative bacteria [Escherichia coli (325), Klebsiella sp.(346), Acinetobacter baumanii complex (37) and Pseudomonas aeruginosa (22)] from 485 patents were tested simultaneously by BMD and Vitek-2 method for colistin susceptibility testing. Results: The Essential agreement (EA), Categorical agreement (CA), Very major error (VME) and Major error (ME) rates for Klebsiella sp. were 87.3%, 89.3%, 8% and 2.3% respectively, for Escherichia coli were 88.3%, 89.5%, 9.2% and 1.2% respectively, for Acinetobacter baumannii complex were 89.1%, 91.8%, 8.1% and 0% respectively, for Pseudomonas aeruginosa were 68.1%, 72.7%, 0% and 27.2% respectively. Conclusions: Colistin susceptibility testing by Vitek-2 method is an easily adoptable method and the results of Vitek-2 with reference to BMD are acceptable to a great extent in Klebsiella sp., Escherichia coli and Acinetobacter baumanii complex. So, we believe that Vitek-2 method may be used for colistin susceptibility testing in low risk patients. However, BMD should be used in high risk immunosupressed and immunocompromised patients who are admitted in critical care units. For Pseudomonas aeruginosa, BMD should be routinely used.